Strategi Pengembangan Agribisnis Sayuran Skala Kecil Berbasis Pemanfaatan Lahan Kosong Di Desa Muara Danau - Agus Nuramal; Rintan Milia Sari; Bintang Tiara Diva Azzahra; Dwinaya Ramadhini; Suyanti Suyanti (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Muara Danau Village has numerous vacant plots surrounding residents’ homes that have historically been left to grow wild or used only sporadically without productive management, even though residents still largely rely on purchasing vegetables to meet their daily needs. This Community Service Program (KKN) aimed to encourage residents to utilize these vacant plots for vegetable cultivation through a participatory approach ranging from land inventory and outreach to practical planting training and guidance on demonstration plots. Activities were conducted across three types of land settings reflecting local conditions: semi-shaded home gardens, open land, and limited spaces utilizing polybags; trial crops included water spinach (kangkung), mustard greens (sawi), and bird’s-eye chili (cabai rawit). Results indicated a significant improvement in residents’ understanding of vegetable cultivation techniques and their habits regarding the recording of costs and yields compared to pre-training levels. Participants subsequently formed small groups to manage communal gardens and began initiating sales of their produce to local village shops and via social media. Despite facing challenges such as water scarcity during the dry season and limited market reach, the program successfully fostered an awareness among residents that vacant land around their homes could serve as both a food source and a means of generating additional family income.